2020
DOI: 10.1016/j.sjbs.2019.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 4-CPPU on in vitro multiplication and sustainable generation of Hibiscus rosa-sinensis L. ‘White Butterfly’

Abstract: There are more than nine thousand cultivars of Hibiscus rosa-sinensis L., with a series of flowers with shapes, colors and new cultivars continues as generated through both traditional and modern breeding techniques. In this study, advanced biotech methods of in vitro culture have been used to identify a technique for the efficient mass multiplication of H. rosa-sinensis ‘White Butterfly’, using phenyl urea, N-(2-Chloro-4-pyridyl)-N′-phenylurea (4-CPPU). For the first time, the effects of 4-CPPU for stimulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…This response might be linked to the excessive callus formation on explants from these BAP treatments that could lead to limited nutrient supply and subsequent death of explants. Faisal et al (2020) also reported that high cytokinin concentrations stimulated callus growth and decreased the regeneration potential of H. rosa-sinensis explants. More frequent transferring onto fresh MS medium could alleviate the problem (Bhalla et al, 2009;Davies et al, 2017).…”
Section: Bap Concentration and The Type Of Explantmentioning
confidence: 91%
See 2 more Smart Citations
“…This response might be linked to the excessive callus formation on explants from these BAP treatments that could lead to limited nutrient supply and subsequent death of explants. Faisal et al (2020) also reported that high cytokinin concentrations stimulated callus growth and decreased the regeneration potential of H. rosa-sinensis explants. More frequent transferring onto fresh MS medium could alleviate the problem (Bhalla et al, 2009;Davies et al, 2017).…”
Section: Bap Concentration and The Type Of Explantmentioning
confidence: 91%
“…Cytokinins are known to enhance cell division, cell elongation and induction of shoots from the nodal meristem of explants cultured in vitro (Sami et al, 2016;Wybouw and De Rybel, 2019). 6-Benzyl-aminopurine (BAP) is reported to be the most effective cytokinin for shoot induction, since it can cause proliferation of more axillary buds in a shorter period of time (Bhalla et al, 2009;Bekircan et al, 2018;Faisal et al, 2020) than others. Micropropagation studies of some Hibiscus species, such as Hibiscus sabdariffa, H. moscheutos and H. rosa-sinensis showed that the shoot induction response depended on the BAP concentration, plant species and explant type (Kumar et al, 2016;Faisal et al, 2020;Lobodina et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genus Hibiscus has more than 250 species, including annual and perennial herbaceous forms and ending with small woody shrubs [1]. Representatives of various species of the genus Hibiscus, due to their attractiveness, are used for landscaping for various purposes, including in coastal areas with a high salt content, and some species are used as raw materials for the preparation of medicines [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…The publications on clonal micropropagation of hibiscus in vitro are extremely rare. There are some results on the reproduction of Hibiscus syriacus L. [12], Hibiscus sabdariffa L. [13], Hibiscus srosa-sinensis L. [1,14]. However, there is no information on in vitro cultivation of Hardy hibiscus.…”
Section: Introductionmentioning
confidence: 99%